Strategi implementasi AI untuk meningkatkan ketersediaan dan aksesibilitas perpustakaan digital - M. Yusuf (Libraria: Jurnal Ilmu Perpustakaan dan Informasi, 2024)
Digital libraries serve as a crucial foundation in the current information era; however, the availability and accessibility of information often encounter challenges. This article presents the implementation strategy of Artificial Intelligence (AI) to enhance the availability and accessibility of digital libraries. The background reflects the central role of libraries in providing knowledge and information to the public. The identification of issues highlights constraints in the management and distribution of digital content that hinder effective access. The research method employed library research, exploring literature related to AI implementation in the context of digital libraries. The research objective is to formulate practical and effective strategies to improve the availability and accessibility of information in digital libraries. The results encompass recommendations for the use of AI technology in collection management, personalized recommendation systems, and data security integration. The implementation of these strategies is expected to strengthen the role of digital libraries in meeting the information needs of modern society.